Urgensi Penyelenggaraan Bantuan Hukum Bagi Masyarakat Miskin Oleh Pemerintah Daerah - Baital, Bachtiar (SALAM: Jurnal Sosial dan Budaya Syar-i, 2016)
Abstract: Implementation of legal assistance by local governments that are formalized into a regional regulation is essential in order to ensure and realize equality before the law and access to justice for everyone, especially the poor as vulnerable groups with legal problems. For local governments, the provision of legal aid is a form of commitment and political will of local governments within the framework of regional autonomy aimed at providing protection to their citizens, one of which relates to access to justice as the principle of equal treatment in the face of law and government with no exception as set forth in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia.Keywords: Legal Aid, Poor People, Local GovernmentÂ Abstrak: Penyelenggaraan bantuan hukum oleh pemerintah daerah yang diformilkan ke dalam suatu peraturan daerah sangat diperlukan dalam rangka untuk menjamin dan mewujudkan persamaan dihadapan hukum dan akses pada keadilan bagi setiap orang terutama masyarakat miskin sebagai kelompok masyarakat yang rentan bermasalah dengan hukum. Bagi pemerintah daerah, penyelenggaraan bantuan hukum merupakan bentuk komitmen dan political will pemerintah daerah dalam kerangka otonomi daerah yang ditujukan untuk memberikan perlindungan kepada warganya, salah satunya berkaitan dengan akses pada keadilan sebagai pengejewantahan prinsip perlakuan yang sama di hadapan hukum dan pemerintahan dengan tanpa kecuali sebagaimana dituangkan dalam Pasal 27 ayat (1) UUD NRI Tahun 1945.Kata Kunci: Bantuan Hukum, Masyarakat Miskin, Pemerintah Daerah